Neighbour effects in maize/okra mixed cropping - ADELANA, B. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Maize (Zea mays L.) and okra (Abelmoschus esculentus L. Moench) were grown in pure and mixed stands with the mixtures having the same plant density as the pure stands. The sole crops gave higher yields than in mixtures. There was competition for growth factors between the two species with their relative yield total (RYT) slightly above unity. The taller maize was at an advantage in the mixture and its yield was only slightly reduced compared with the pure stand, white the shorter okra plants were heavily shaded and the yield greatly reduced. Planting both crops together was more efficient as their land equivalent ratio was above unity.